Some Considerations about the Role of "Private Right" of the Doctrine of Right in the Kantian Philosophy of the State - Tomassini, Fiorella (2014)
The  purpose  of  this  paper  is to  examine  the  role  of  the  section  “Private  right”  of  Kant’s Doctrine of Right.  I propose that the analysis of “the external mine and thine”, which takes place in this section, has the function of proving that there is a kind of subjective right related to the possession of external objects of choice: the acquired rights. These rights, as well as the innate right, require for their effective exercise the foundation of a state legislated by the general will.